Exploration of Resident Satisfaction and Willingness in the Renovation of a Typical Old Neighborhood - Wenjun Peng; Yanyan Huang; Changquan Li; Yilin Wang (Buildings)
The reconstruction of old communities makes an outstanding contribution to, and holds practical significance for, livelihoods and ecological civilization in the urban renewal context. Clarifying the renovation intentions of residents is conducive to the effective implementation of reconstruction projects. This paper takes a typical old neighborhood in Wuhan as an example to survey residents’ living satisfaction and renovation intention. Multiple linear regression analysis, factor analysis, and correlation analysis were used to quantitatively screen, judge, and process sample data. The results show that residents’ living satisfaction and willingness to renovate were different under the dimensions of resident age and property rights, respectively. Most residents were dissatisfied with the living state of the neighborhood. Residents over 61 years old or those who held real estate certificates had a strong willingness to renovate and tended to accept a unified management manner after the renovation of the old neighborhood. Moreover, resident satisfaction with the internal road traffic, infrastructure, and building state significantly affected the residents’ overall satisfaction with the living environment in the old neighborhood, which should be given more attention to improve the residents’ willingness to support the renovation items. Furthermore, it was found that resident satisfaction with building conditions, infrastructure, internal road traffic, and public environment significantly impacted their agreement with the renovation in the old neighborhood. This investigation could provide a basis and guidance for the reconstruction and design of old communities.